2010
DOI: 10.1577/t08-185.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Variable Interannual Summer Water Temperatures on Brook Trout Growth, Consumption, Reproduction, and Mortality in an Unstratified Adirondack Lake

Abstract: Stressful water temperatures negatively affect physiological processes in fishes, yet evidence for how elevated temperatures influence population-level characteristics is rare. An 8-year field study of brook trout Salvelinus fontinalis in an unstratified Adirondack lake revealed that an aggregate measure of chronically stressful summer water temperatures strongly influenced brook trout population-level characteristics. We quantified chronic thermal stress using the cumulative degree-days over which bottom temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 61 publications
(88 reference statements)
4
51
2
Order By: Relevance
“…Quist et al (2004) suggested that elevation acts as a proxy for temperature, which influences the survival, growth, reproduction, and distribution of fish (Buisson et al 2008;Lyons et al 2010;Robinson et al 2010). Although elevation probably does not act as a surrogate measure for temperature in Iowa, differences in elevation likely correspond to differences in underlying geology and climate across the state.…”
Section: Discussionmentioning
confidence: 99%
“…Quist et al (2004) suggested that elevation acts as a proxy for temperature, which influences the survival, growth, reproduction, and distribution of fish (Buisson et al 2008;Lyons et al 2010;Robinson et al 2010). Although elevation probably does not act as a surrogate measure for temperature in Iowa, differences in elevation likely correspond to differences in underlying geology and climate across the state.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of suitable thermal habitat affects total sustained yield of fish in temperate lakes (Christie and Regier 1988), and in salmonids, high temperatures may affect several physiological processes detrimentally, including feeding, growth, and reproduction (Myrick and Cech 2000;Pankhurst and King 2010;Robinson et al 2010). Fish can avoid detrimental warm temperatures in thermally stratified lakes by occupying the cooler hypolimnion, but only if the oxygen regime is favourable (Budy et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The weak influence of stream temperature may be due to the fact that study sites were mostly thermally suitable for brook trout. Hartman and Cox (2008) reported that metabolic rates of brook trout declined sharply above 20°C in a laboratory setting, and wild brook trout populations suffer when stream temperature exceeds 20°C for an extended period (Stranko et al 2008;Robinson et al 2010). In comparison, summer mean temperature in 2008 was 18.7°C (5th to 95th percentiles: 17.8-19.2°C) in JHSB and 19.0°C (18.0-21.0°C) in KFB, and stream temperature was lower in 2009 (Table 1).…”
Section: Discussionmentioning
confidence: 99%